2013
DOI: 10.5489/cuaj.1320
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a 6 Fr catheter in women: Are they obstructive?

Abstract: Objectives: Our objective was to evaluate the effect of a 6 Fr transurethral catheter on the uroflowmetry and to assess whether it potentially contributes to the bladder outlet obstruction (BOO) in women. Methods: We reviewed the charts of 1367 women who underwent an urodynamic study. We included patients with a non-invasive free-flow study (NIFFS) and pressure flow study (PFS) performed through a 6 Fr double lumen transurethral catheter. Results: In total, 120 women met the inclusion/exclusion criteria. Mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…In addition, the catheter blocks free flow of fluid out of the bladder and may cause non-physiologically high bladder pressures and low flow. [2][3][4][5] This underlines the importance of a catheter-free methodology for measuring voiding bladder pressures. We hypothesize that, using pressure dependent acoustic properties of ultrasound (US) contrast microbubbles (MBs), we can measure voiding bladder pressure without a catheter.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, the catheter blocks free flow of fluid out of the bladder and may cause non-physiologically high bladder pressures and low flow. [2][3][4][5] This underlines the importance of a catheter-free methodology for measuring voiding bladder pressures. We hypothesize that, using pressure dependent acoustic properties of ultrasound (US) contrast microbubbles (MBs), we can measure voiding bladder pressure without a catheter.…”
mentioning
confidence: 91%
“…However, due to catheter related anxiety and discomfort and/or complete occlusion of urethra, not all patients can void. In addition, the catheter blocks free flow of fluid out of the bladder and may cause non-physiologically high bladder pressures and low flow 2–5 . This underlines the importance of a catheter-free methodology for measuring voiding bladder pressures.…”
mentioning
confidence: 99%
“…Besides the stress of being examined, the presence of urethral catheters has been broadly reported to influence the values of maximum flow rate during pressure‐flow study (PFS) 4 . This observation has been confirmed in female population 5,6 and in a myriad of clinical conditions 7 . The size of the catheter seems to be one of the factors explaining this phenomenon but not the only one 8,9 .…”
Section: Introductionmentioning
confidence: 97%
“…They found that urodynamics for identifying BOO was inferior and actually falsely elevated the number of women with BOO. 1 This situation is not isolated to the over-diagnosis of BOO by obstructing catheters. Many other lower urinary tract problems are also difficult to demonstrate reliably and consistently on urodynamics.…”
mentioning
confidence: 99%
“…Richard and colleagues suggest that there may be issues with using a pressure flow study (PFS) to diagnose bladder outlet obstruction (BOO) in women. 1 They clearly demonstrate that a 6 French catheter used during a PFS can be obstructive and over-diagnose BOO in over 11% of women. They found that urodynamics for identifying BOO was inferior and actually falsely elevated the number of women with BOO.…”
mentioning
confidence: 99%